What Models and Tools can Contribute to a Better Understanding of Brain Activity? - Goodfellow, Marc; Andrzejak, Ralph G.; Masoller, Cristina; Lehnertz, Klaus (Frontiers in Network Physiology, 2022)
Despite significant progress in understanding structure and function of the human brain, our knowledge of how the dynamics of brain networks arise is far from complete. An improved interpretation of brain activity at its wide range of temporal and spatial scales are urgently needed. Here we discuss, from an interdisciplinary network perspective, the advancements in physical and mathematical modeling as well as in data analysis techniques that, in our opinion, are required to further advance our understanding of brain structure and function.